Towards improved performance of waterborne polymer dispersions through creation of dense ionic interparticle network within their films. (16th January 2023) - Argaiz, Maialen; Aguirre, Miren; Tomovska, Radmila
Abstract: To overcome the main challenge of low performance of the waterborne polymer coatings due to the particulate nature of the polymer dispersions and the complex film formation process, in this work we implemented the strategy of ionic complexation between oppositely charged waterborne polymer particles. For that aim, doubled charged ionic monomers ithaconic acid (IA) and styrenic 1, 4-diazabicyclo[2.2.2]octane (DABCO) were used to densely functionalize (meth)acrylic film forming polymer particles, synthesized by seeded semi-batch emulsion polymerization to produce high solids content anionically and cationically charged polymer dispersions, respectively. The main advantage of the double charges in the selected ionic monomers is that they provide high ionic charge density onto charged particles at lower content of ionic monomers. The blending of these oppositely, densely charged and concentrated dispersions resulted in instantaneous coagulation. To postpone the immediate complexation, water-soluble non-ionic polymeric stabilizing species as steric obstacles around the colloids were employed, which allowed to prepare colloidally stable blends and to prepare ionic complexed films. Certainly, the established ionic complexes between carboxylic acids of IA anionic monomer and quaternary ammonium groups of DABCO units within the films improved substantially the mechanical properties and the water sensitivity of the ionic complexed polymeric films with respect to individual films and the reference blend, in which ionic bonding was prevented by pH control. Moreover, the dense ionic network formed within the film actuated as a strong barrier to the leakage of all the water-soluble species during film immersion in water. Beside simple strategy towards improved performance of waterborne coatings, these results offer further extension of their application potential. Graphical abstract: Image 1 Highlights: Anionic and cationic double charged polymer dispersions were synthesized. Blends of oppositely and densely charged dispersions coagulated after mixing. Tree-block copolymer non-ionic stabilizers avoided immediate coagulation. Ionic complex blend films have enhanced mechanical and water resistance.